2022
DOI: 10.3390/biology11060854
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Symbiosis Leads to Differential Regulation of Genes and miRNAs Associated with the Cell Wall in Tomato Leaves

Abstract: Arbuscular mycorrhizal symbiosis is an association that provides nutritional benefits to plants. Importantly, it induces a physiological state allowing plants to respond to a subsequent pathogen attack in a more rapid and intense manner. Consequently, mycorrhiza-colonized plants become less susceptible to root and shoot pathogens. This study aimed to identify some of the molecular players and potential mechanisms related to the onset of defense priming by mycorrhiza colonization, as well as miRNAs that may act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
2
2
0
Order By: Relevance
“…Roots were maintained in lactoglycerol 1:1:1 (water/lactic acid/glycerol) and observed by light microscopy (BOECO Germany, BM-180). Mycorrhizal colonization was confirmed as previously reported by Mendoza-Soto et al (2022) .…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Roots were maintained in lactoglycerol 1:1:1 (water/lactic acid/glycerol) and observed by light microscopy (BOECO Germany, BM-180). Mycorrhizal colonization was confirmed as previously reported by Mendoza-Soto et al (2022) .…”
Section: Methodssupporting
confidence: 84%
“…After infection with the pathogen Xanthomonas campestris showed increased in resistance compared to non-colonized plants ( Liu et al, 2007 ). These data are in agreement with an RNA-seq analysis in which cell wall biogenesis-related genes, including some XTHs , were differentially regulated in leaves of AM tomato plants in parallel with an increase in resistance against the shoot pathogen Sclerotinia sclerotiorum ( Cervantes-Gámez et al, 2016 ; Mendoza-Soto et al, 2022 ). This supports the idea that cell wall modification genes, including XTHs , play an essential role in shoots of AM-colonized plants to trigger a priming mechanism that improves defense against subsequent pathogen attacks.…”
Section: Introductionsupporting
confidence: 89%
“…Elsharkawy et al ( 2012 ) obtained similar results in cucumber when they applied dual inoculation of Glomus mosseae and Fusarium equiseti (GF18-3) to control CMV; the absorbance values of ELISA detection for G. mosseae and GF18-3-treated plants were significantly reduced as compared to F. equiseti- treated alone at 7 and 14 dpi. Most recently, in tomato plants, the efficient biocontrol activity of AM colonization against ToMV infection was validated by Mendoza-Soto et al ( 2022 ), which led to a marked decline in the viral accumulation level. On the contrary, Fakhro et al ( 2010 ) revealed that the utilization of Piriformospora indica as a biocontrol agent increased the accumulation of Pepino mosaic virus (PepMV).…”
Section: Resultsmentioning
confidence: 97%
“…AM fungi also provide a physiological state that enables plants to react more quickly and forcefully to pathogen attacks. According to Mendoza-Soto et al ( 2022 ), tomato plants with AM colonization are less vulnerable to the Tomato mosaic virus (ToMV). Maffei et al’s study ( 2014 ) showed a clear protective role of AM fungi against viral infections in roots and shoots and in disease symptoms, where during the early stages, decreased or no difference in the severity of symptoms was detected in AM plants compared to non-AM ones.…”
Section: Introductionmentioning
confidence: 99%